2021
DOI: 10.1111/cas.15007
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous expression of endoglin marks advanced renal cancer with distinct tumor microenvironment fitness

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, it should be mentioned that c-Ski may accelerate cancer progression mainly through the suppression of TGF-β-dependent Smad signaling, and not through the suppression of BMP-dependent Smad signaling in an experimental setting. Our latest data also indicated that endoglin expression was heterogeneously upregulated in highly malignant derivatives obtained after serial transplantation of human RCC cells ( Momoi et al, 2021 ).…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 81%
“…However, it should be mentioned that c-Ski may accelerate cancer progression mainly through the suppression of TGF-β-dependent Smad signaling, and not through the suppression of BMP-dependent Smad signaling in an experimental setting. Our latest data also indicated that endoglin expression was heterogeneously upregulated in highly malignant derivatives obtained after serial transplantation of human RCC cells ( Momoi et al, 2021 ).…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 81%